Karakterisasi Fenotipe dan Genotipe Anggrek Phalaenopsis amabilis (L.) Blume Transforman Pembawa Konstruksi UBI::Cas9::U3::PDS3 - Andani Kesuma, Amarilis; Nopitasari, Sri; Yoshioka, Yasushi; Matsumoto, Shogo; Semiarti, Endang (Jurnal Hortikultura Indonesia, 2020)
Phalaenopsis amabilis (L.) Blume is an Indonesian national “Flower of Charm” (“Puspa Pesona”), an ornamental plant that by using genetic engineering we could improve the flower quality. In this study, Agrobacterium tumefaciens-mediated genetic transformation and CRISPR/Cas9 genome editing system was used to edit the orchid genome more specific and precisely. Twelve months old putative transgenic plants originated from protocorm like bodies (PLBs) transformation harboring the T-DNA construct UBI::Cas9::U3::PDS3/plasmid pRGEB32. Proofing for the putative transformant plants were stably harboring the T-DNA constructs were conducted by genotype and phenotype characterization. The purpose of this study was to characterize genotypically and phenotypically the putative transformant of P. amabilis harboring T-DNA constructs UBI::Cas9::U3::PDS3 compared to non-transformant. Genotype characterization was carried out by detecting the integration of T-DNA harboring UBI::Cas9::U3::PDS3 on the P. amabilis genome using several primers for HPT, Cas9, PDS3 and trnL-F (internal control primers). Phenotype analysis was carried out by observing and analyzing chlorophyll content using spectrophotometric methods. The results showed that genome of putative P. amabilis transformant age 12 months could be amplified by the primers. Phenotypic analysis of P. amabilis transformant showed a change in plant color from green to pale (albino) with lower chlorophyll content compared to non-transformant. This indicates that the CRISPR/Cas9 technology is able to edit the genome of orchids. Keywords: Chlorophyll, CRISPR/Cas9, orchid, Phalaenopsis amabilis (L.) Blume, PHYTOENE DESATURASE 3 (PDS3), Transformant.